The Role of Strengthening Religious Moderation on People’s Economic Development in Naga Juang District, Mandailing Natal Regency - Affandi, Faisal; Mukhlis, Mukhlis; Saputra, Muhammad Ari; Marzuki, Datuk Imam (Budapest International Research and Critics University, 2022)
This study to identify the strengthening of religious moderation and examine its relationship to the development of the people's economy in Naga Juang District, Mandailing Natal District. This study used a qualitative research method with a case study approach. This research was conducted in Naga Juang District, Mandailing Natal District. The Chief of Villages and Religious Leaders Naga Juang District. Data collection techniques used in this study include; observation, interview, documentation, focus discussion group (FGD). The results of this study indicate that the strengthening and application of religious moderation in Naga Juang District which has been going on so far has been going well. The community, religious leaders/community and the District Government have synergized with each other to strive to uphold a balanced and fair attitude in implementing values and teachings. the teachings of their respective religions. The existing economic facilities and infrastructure in Naga Juang District are still very limited. The majority of people who depend on the agricultural sector for their lives, responding to this, the District Government, Community/Religious Leaders and the community began to utilize protected forests in the Naga Juang District area to improve people's living standards while still paying attention to applicable laws and regulations and still paying attention to environmental sustainability.